Growth Performance and Nutrient Utilization of Male Broiler Chicken as Affected by Feed Restriction with or without Garlic Supplementation - Singh, Vishavdeep; Singh, Udeybir; Sethi, A.P.S.; Lamba, J.S. (Indian Journal of Animal Nutrition, 2019)
An experiment was conducted to study the effects of feed restriction and garlic supplementation on growth performance weekly and nutrient utilization in male broilers. In this study, 120, day old male broilers were randomly distributed into 5 treatments each having 4 replicates with 6 birds in each replicate. Diets were formulated as per ICAR 2013 specifications and were fed in 3 phases. Treatment T1 was served as control. The other treatments comprised: T2 = T1 with feed restriction (10-12 h) at 8-17 days of age (DOA) with garlic supplementation, T3 = T1 with feed restriction at 8-17 DOA (10-12 h) without garlic supplementation, T4 = T1 with feed restriction at 18-27 DOA (10-12 hrs) with garlic supplementation, T5 = T1 with feed restriction at 18-27 DOA (10-12 hrs) without garlic supplementation. Early feed restriction (8-17 DOA) with or without garlic supplementation reduced (P